A disease with many faces - Caires, Nídia (Breathe (Sheff), 2019)
Can you diagnose this man with progressively worsening shortness of breath, mucous productive cough, weight loss, fatigue and a history of suspected pulmonary tuberculosis? http://bit.ly/2VUdnTr